Is antenatal clinic attendance associated with essential newborn care practices in women who deliver at home in five districts of southern tanzania?. (4th April 2011) - Blencowe, H J; Schellenberg, J
Abstract : Aims: Most of the 3.6 million annual neonatal deaths occur at home in low-income countries and are preventable. Optimal newborn care practices can reduce neonatal mortality, but uptake globally remains low. Antenatal clinic (ANC) may provide a vehicle for communicating behaviour change to increase coverage of these practices. We aim to determine whether full ANC attendance is associated with positive newborn care practices in Tanzanian women giving birth at home. Methods: A secondary analysis of a survey including all households in five districts of Southern Tanzania in 2007 was undertaken (93% response rate). 91% of 13–49 year old women from these households had been interviewed about their last pregnancy, delivery and post-partum period including 11, 801 women who gave birth at home in the previous 12 months. Reported newborn care practices were compared among those with full or suboptimal ANC attendance. Results: 4052 women (34%) completed full ANC (four visits starting before the sixth month of pregnancy). Reported uptake of newborn care practices varied: 1009 (9%) reported giving birth with a skilled attendant, 1937 (16%) initiated breastfeeding in the first hour of life, 11 024 (93%) used a clean blade to cut the cord. Women who completed ANC were more likely to report having a birth attendant with clean hands (adjusted OR (aOR)=1.2 (95% CI 1.1 to 1.3; p<0.001)), using a clean cord tie (aOR=1.1 (1.1–1.2, p=0.001)) and exclusively breastfeeding (aOR=1.1(1.0–1.2, p=0.02)). Those attending ANC were less likely to report cutting the cord using a clean blade (aOR=0.8 (0.7–1.0, p=0.06)). There was no association between ANC and other newborn care practices studied. Conclusions: Suboptimal newborn care practices were frequently reported. There was a small but statistically significant association between ANC and some newborn care practices. If these findings represent a true effect, rather than being due to chance, bias or unresolved confounding, even a small improvement in newborn care practices may represent an important effect at a public health level and lead to reductions in neonatal mortality. Widespread innovation enabling improvement of quality, methods and time given to counselling and interventions aimed at behaviour change within ANC may further improve its effectiveness for newborn care practices.